DIVIDEND POLICY AS MODERATOR OF FIRM VALUE DETERMINANTS - Inrawan, Ady (ULTIMA Management, 2025)
Abstract- This study is to analyze the influence of leverage, firm size, and profitability on firm value, with dividend policy as moderator. Secondary data were used, consisting of financial reports gathered from the Indonesia Stock Exchange (IDX). The study’s population consists of 67 firms listed in the LQ45 Index between 2019-2023. By applying purposive sampling, 19 companies chosen, resulting in 95 total observations. The data analysis utilized is multiple linear regression incorporating a moderating variable (Moderated Regression Analysis/MRA), performed on panel data using EViews 13 software. The selection of the analytical model was validated through the Chow Test, the Hausman Test, and the Lagrange Multiplier Test. The findings indicate that leverage  has a negative effect on firm value, while profitability has a positive effect. In contrast, firm size has no significant effect on firm value , the findings indicate that dividend policy moderates the relationship between profitability and firm value. However, dividend policy does not moderate the relationship between leverage or firm size and firm value. These findings suggest that while dividend policy can enhance the positive impact of profitability on firm value, it is insufficient to mitigate the negative effect of leverage or to strengthen the insignificant impact of firm size on firm value Keywords: Firm Value; Leverage; Firm Size; Profitability; Dividend Policy